Neuroprotective Activity of Premna Latifolia on Streptozotocin Induced Diabetic Neuropathy in Rats (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The leaves of plant Premna latifolia Lam. traditionally used for the treatment of diabetes and related complications. Presently ethanolic extract of leaves of plant Premna latifolia explored for the neuroprotective potential in rat model of Streptozotocin induced diabetic neuropathy. Streptozotocin was administered 60 mg/kg body weight by the route intra-peritoneal to induce experimental diabetes, then treatment were not given for two weeks to develop diabetic complications. After two weeks of induction, animals treated with extract 100 and 200mg/kg per day for the duration of five weeks. Neuroprotective effect was evaluated by eddy's hot plate and tail immersion. Also by measuring blood sugar and cytokines that cause inflammation likes interleukins, tumor necrosis factor, and nerve growth factor in sciatic nerve. Thiobarbituric acid reactive substances, reduced glutathione and activity levels of catalase, superoxide dismutase, glutathione peroxidase and glutathione reductase measured in the sciatic tissue. Extract normalizes blood glucose in diabetic neuropathy rats brought on by streptozotocin. The diabetic neuropathy rats show significant reductions in the paw licking or jumping time and tail withdrawal time. In these rats pro-inflammatory cytokines level in sciatic nerve was significantly high. In addition, the oxidative stress bio-markers level altered significantly in sciatic nerve tissue. Diabetic neuropathy developing rats treated with extract for five weeks reduce the levels of nerve growth factor, oxidative stress indicators, and pro-inflammatory cytokines rise in the sciatic nerve tissue. Ethanolic extract of Premna latifolia possesses neuroprotective action in STZ-induced diabetic neuropathy.